(untitled) (Research, Society and Development, 2020)
Objective: To primarily evaluate the immediate effect of ischemic compression therapy (ICT) on pain, mobility and strength of shoulder muscles in individuals with Subacromial Impingement Syndrome (SIS). Secondly, to assess whether the strength and mobility assessment protocol influences the amount of MTPs. Methods: A single-arm study with a total of 15 individuals (6 women and 9 men, 34.4±10.43 years; 24.20±2.18 kg/m2) with clinical symptoms of unilateral SIS. All individuals were assessed for the amount of MTPs in the upper trapezius, lower trapezius, supraspinatus, infraspinatus, pectoralis minor and middle deltoid muscles; pressure pain threshold (PPT) in the upper trapezius, lower trapezius, infraspinatus and middle deltoid muscles; range of motion (ROM) of the shoulder; and isometric strength of shoulder muscles. Results: There was a reduction in the total amount of MTPs (p<0.01) and an increase in the PPT in the middle deltoid muscle (p=0.03) in the comparisons between pre and post treatment, while there was no difference in ROMs (p>0.05) and strength measures (p>0.24); however, the pain was less during the sagittal elevation ROM (p<0.01) and internal rotation (p=0.04), and during the performance of strength in arm elevation and external rotation (p=0.01). There was generally no difference in the variables assessed between baseline and pre-treatment (p>0.06). Conclusion: The ICT immediately reduced the amount of MTPs and pain during mobility and strength, but did not change the PPT, ROM or strength variables. The evaluation of mobility and strength did not have a negative effect on the evaluated variables.